Formal shifts from poetry to prose (Journal of the College of Basic Education, 2023)
Summary of the researchThe Arabic poem has undergone many transformations due to the continuous changes that societies undergo, starting with the demolition of the traditional template represented by the pillar of Arabic poetry, through many attempts and experiments that had an effective role in liberating Arabic poetry from the restrictions of imitation and dependency, and ending with the birth of poetic texts steeped in experimentation and ambiguity.Keywords: transformation, poetry, prose.Abstract Research: (Text Transformations in Modern Iraqi Poetry / Muhammad Turki Al-Nassar as a Model)